2018
DOI: 10.3390/nano8060382
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Cytotoxic Potential of Biosynthesized Silver Nanoparticles by Some Plant Extracts

Abstract: The provision of nanoparticles using biogenic material as a part of green chemistry is an attractive nanotechnology. The current research aimed to test the antimicrobial and cytotoxic efficacy of silver nanoparticles synthesized by extracts of Phoenix dactylifera, Ferula asafetida, and Acacia nilotica as reductant and stabilizing agents in silver nanoparticle formation. Synthesized nanoparticles were evaluated for their antimicrobial activity against Staphylococcus aureus (Gram-positive) and Pseudomonas aerugi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 53 publications
7
63
0
Order By: Relevance
“…Interactions between metabolites in the extract and metal ions cause the bioreduction of metal salts and synthesis of nanoparticles. The functional groups in the plant extract act as reducing, capping, and stabilizing agents [58,68]. Negatively charged (COO − ) and polar (OH and CO) groups presented in the plant extract attach on the Ag surface with high tendency and contribute in both reduction and stabilization of AgNPs [69].…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 99%
“…Interactions between metabolites in the extract and metal ions cause the bioreduction of metal salts and synthesis of nanoparticles. The functional groups in the plant extract act as reducing, capping, and stabilizing agents [58,68]. Negatively charged (COO − ) and polar (OH and CO) groups presented in the plant extract attach on the Ag surface with high tendency and contribute in both reduction and stabilization of AgNPs [69].…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 99%
“…Over 50% of all modern clinical drugs are of natural product origin and natural products play an important role in drug development programs in the pharmaceutical industries. [2,3] Acacia nilotica (Babul tree) is the member of the family Mimosaceae; Acacia nilotica is multipurpose nitrogen fixing tree legume. It is widely spread in subtropical and tropical Africa from Egypt to Mauritania southwards to South Africa, and in Asia eastwards to Pakistan and India.…”
Section: Introductionmentioning
confidence: 99%
“…The pH 8 (20%) 6.0x10 9 4.8x10 9 4.8x10 9 4.8x10 9 4.8x10 9 more than 100 nm, and with a negative zeta potential (Mohammed et al, 2018;Singh et al, 2015). Kokila et al (2016) showed that silver nanoparticles synthesized from Carica papaya bark extract had great stability due to their coating.…”
Section: Discussionmentioning
confidence: 99%